2018
DOI: 10.1186/s13046-018-0695-5
|View full text |Cite|
|
Sign up to set email alerts
|

Flavagline analog FL3 induces cell cycle arrest in urothelial carcinoma cell of the bladder by inhibiting the Akt/PHB interaction to activate the GADD45α pathway

Abstract: BackgroundProhibitin 1 (PHB) is a potential target for the treatment of urothelial carcinoma of the bladder (UCB). FL3 is a newly synthesized agent that inhibits cancer cell proliferation by targeting the PHB protein; however, the effect of FL3 in UCB cells remains unexplored.MethodsFL3 was identified to be a potent inhibitor of UCB cell viability using CCK-8 (cell counting kit-8) assay. Then a series of in vitro and in vivo experiments were conducted to further demonstrate the inhibitory effect of FL3 on UCB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…These results indicate that down regulation of Akt1/2 level in DLBCL cells exposed to FL3 may be mediated at least by reduction of AKT mRNA levels and by a caspase-dependent cleavage of the protein. Finally, as PHBs are known to be substrates of Akt [36, 37], we indirectly analyzed PHB1 phosphorylation and our results strongly suggest decreased PHB phosphorylation in FL3-treated DLBCL cells (Additional file 1: Figure S6).
Fig.
…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…These results indicate that down regulation of Akt1/2 level in DLBCL cells exposed to FL3 may be mediated at least by reduction of AKT mRNA levels and by a caspase-dependent cleavage of the protein. Finally, as PHBs are known to be substrates of Akt [36, 37], we indirectly analyzed PHB1 phosphorylation and our results strongly suggest decreased PHB phosphorylation in FL3-treated DLBCL cells (Additional file 1: Figure S6).
Fig.
…”
Section: Resultsmentioning
confidence: 88%
“…In this study we used the flavagline FL3 to gain insight into the cytoplasmic role of PHBs in DLBCL cells. Indeed, by binding to PHB, flavaglines were shown to inhibit PHB-mediated signaling pathways, and this interaction did not target mitochondria [36, 43]. As expected, FL3 triggered apoptosis of DLBCL cell lines and also in vivo in a xenograft murine model.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous work showed that growth arrest and DNA damage-inducible 45 alpha gene (GADD45a) may play a repressive role in BC cell proliferation by delaying cell cycle progression in the G2/M phase 3. GADD45a was first found and defined by Fornace et al in 1989 when researchers found that some mRNAs were increased after exposure to a variety of exogenous and endogenous stresses associated with growth arrest, including ultraviolet (UV) radiation 4.…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms by which FL3 targets cancer cells were reported in the literature. It was shown that in urothelial carcinoma cells, FL3 can directly binds to Prohibitin 1 (PHB) preventing its phosphorylation by Akt, leading to a decrease of PHB in mitochondria, which causes a mitochondria-related apoptosis and cell cycle inhibition 5 , 6 . PHB is an ubiquitous and evolutionarily conserved protein expressed in different cellular compartments including the nucleus, cytoplasm and mitochondria 7 , it is involved in diverse biological processes such as cell proliferation, resistance to apoptosis, maintenance and integrity of mitochondria 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%